2010
DOI: 10.1111/j.1399-0012.2009.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, multicenter study evaluating early corticosteroid withdrawal with Thymoglobulin® in living‐donor kidney transplantation

Abstract: rATG with tacrolimus and MMF therapy may allow early elimination of corticosteroids, is associated with trends toward lower lipid levels, less weight gain, and a safety profile comparable to CCST therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 11 publications
4
68
0
Order By: Relevance
“…Compared with conventional steroid use, when TAC and MPA were used, the no-steroid arm was not associated with higher acute rejection (RR, 1.06; 95% CI, 0.79 to 1.42), death (RR, 1.09; 95% CI, 0.50 to 2.37), and graft loss (RR, 1.29; 95% CI, 0.71 to 2.34). Similar findings were observed in a prospective, randomized multicenter trial (Thymoglobulin in Renal Transplantation for Induction and Minimization of Steroids study, n=153), which evaluated early corticosteroid withdrawal in LRT recipients who received r-ATG induction and TAC/MPA maintenance (8). In another steroid withdrawal randomized controlled trial (TAC/MPA maintenance regimen), Hanaway et al stratified recipients based on their immunologic risk; low-risk patients (n=335) were randomized to alemtuzumab or basiliximab, whereas high-risk patients (n=139) received alemtuzumab or r-ATG (34).…”
Section: Steroid Avoidancesupporting
confidence: 63%
See 1 more Smart Citation
“…Compared with conventional steroid use, when TAC and MPA were used, the no-steroid arm was not associated with higher acute rejection (RR, 1.06; 95% CI, 0.79 to 1.42), death (RR, 1.09; 95% CI, 0.50 to 2.37), and graft loss (RR, 1.29; 95% CI, 0.71 to 2.34). Similar findings were observed in a prospective, randomized multicenter trial (Thymoglobulin in Renal Transplantation for Induction and Minimization of Steroids study, n=153), which evaluated early corticosteroid withdrawal in LRT recipients who received r-ATG induction and TAC/MPA maintenance (8). In another steroid withdrawal randomized controlled trial (TAC/MPA maintenance regimen), Hanaway et al stratified recipients based on their immunologic risk; low-risk patients (n=335) were randomized to alemtuzumab or basiliximab, whereas high-risk patients (n=139) received alemtuzumab or r-ATG (34).…”
Section: Steroid Avoidancesupporting
confidence: 63%
“…Prospective randomized multicenter studies and retrospective registry analysis demonstrate that no-induction therapy can achieve acceptable acute rejection rates (10%-20% at 1 year after transplant), with allograft and patient survival similar to other induction modalities in living donor renal transplantation (LRT) (7)(8)(9)(10). However, the current Kidney Disease Improving Global Outcomes (KDIGO) Transplant Work Group guidelines recommend IL2-RA as a first-line induction agent in all types of donor-recipient profiles to reduce risk of acute rejection and allograft loss.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of TAC/MPA maintenance regimens with or without steroids, controversy exists with respect to the added benefit of IL2-RA induction therapy on outcomes of renal transplantation. In fact, there are recent data that support that no induction therapy could achieve acceptable acute rejection rates (#20% at 1 year after transplantation), with similar allograft and patient survival compared with IL2-RA induction in the setting of the TAC/MPA maintenance regimen (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Several multicenter randomized control trials, that directly compare the risks and benefits of rapid withdrawal or complete avoidance of steroids with regimens using maintenance steroids, in adult patients after renal transplantation have been published [10][11][12][13][14][15]. Most of these trials have demonstrated no increase in the incidence of acute rejection when steroids are minimized after transplantation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these trials have demonstrated no increase in the incidence of acute rejection when steroids are minimized after transplantation [14]. Data on metabolic and cardiovascular benefits of steroid minimization are less robust although the studies do show a lower need for antihyperglycemic and lipid-lowering agents, lesser weight gain and better triglyceride levels with steroid avoidance [13,15].…”
Section: Introductionmentioning
confidence: 99%